Analisis Pengaruh Atribut Produk Terhadap Keputusan Pembelian Yoghurt Mayummy Di Kecamatan Karanggede, Boyolali - Listiyani, Ayu; , Dra. Wuryaningsih Dwi Lestari, M.M (2016)
This thesis titled Analysis of Product Attributes Against Buying Decision Yoghurt Mayummy in District Karanggede , Boyolali . The purpose of this study was to investigate the behavior of consumers in the form of a purchase decision involved the achievement of corporate objectives . Consumers will consider various factors related to the product , the attributes of the product . The study was conducted at the company's Home Industry Mayummy Food Jaya , a company that produces fermented milk , yoghurt . The population studied is the consumer who has ever bought or ever consume yogurt Mayummy . Used as a sample of 100 respondents were arriving in the District Karanggede , Boyolali . Variables used in this study include product quality , product packaging design , product features , and price . The sampling method using purposive sampling method with descriptive analysis techniques and statistical tests that include : multiple regression analysis , hypothesis testing by t test and f test , and coefficient of determination R2. Product attributes have an influence on purchasing decisions Yoghurt Mayummy in District Karanggede , Boyolali . This is evidenced by the acquisition of statistical calculation results with SPSS.16 program . Based on calculations by t test , tcount the variable quality of the product is greater than ttable ( 2.079 > 1.985 ) , meaning that product quality has positive influence on purchase decisions . tcount on packaging design variables is greater than t able ( 2.616 > 1.985 ) , meaning that packaging design has positive influence on purchase decisions . tcount the variable product features is greater than ttable ( 2.255 > 1.985 ) . It means that the product features positive influence on purchasing decisions . tcount the price variable is greater than t table ( 3.108 > 1.985 ) . That is the price positive influence on purchase decisions . Based on the f test , the result of ( 14.032 > 2.53 ) , meaning that the value F count > F tabel , so all the product attributes ( quality , packaging design , features and price ) jointly influence the purchasing decision . R2 is based on test results obtained on the calculation of 0,345 . That is the product attributes ( quality , packaging design , features and price ) influence purchasing decisions b